Pharmacoeconomics of chronic kidney disease - R. I. Yagudina; A. Yu. Kulikov; V. G. Serpik; G. T. Abdrashitova; M. V. Protsenko (Регуляторные исследования и экспертиза лекарственных средств, 2018)
A pharmacoeconomic study is a comprehensive scientific and research activity, which should take into account specific characteristics of a research subject as well as nosology based on common methodological approaches of pharmacoeconomics,. The growing significance of the results obtained when performing pharmacoeconomic analysis involves higher requirements to the quality pharmacoeconomic studies, which is largely stipulated by the methodology used. The analysis of the features that have influence when conducting pharmacoeconomic studies has been studied as exemplified by chronic kidney disease. The aspects of the choice of effectiveness criteria for pharmacoeconomic analysis when performing the analysis of «cost-effectiveness», when analyzing «impact on the budget», have been described. It has been shown that the specificity of the analyzed disease is reflected at all stages of pharmacoeconomic studies: elaboration of study design, choice of performance criteria, determination of the research costs profile, implementation of particular methods of pharmacoeconomic analysis, interpretation of the results of pharmacoeconomic evaluation. It was found that pharmacoeconomic analysis of renal replacement therapy in patients with chronic kidney disease is the most specific.